A new mulinane diterpenoid from the cushion shrub Azorella compacta growing in Perú - Salgado, Francisco (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Azorella compacta is a rare yellow-green compact resinous cushion shrub growing from the high Andes of southern Perú to northwestern Argentina, and which is a producer of biologically active and unique diterpenoids. OBJECTIVE: This study investigated the secondary metabolites present in a Peruvian sample of Azorella compacta and the evaluation of gastroprotective activity of the isolated compounds in a gastric- induced ulcer model in mice. MATERIAL AND METHODS: Six secondary metabolites (diterpenoids 1-6) present in the dichloromethane (DCM) extract of A. compacta growing in Perú were isolated by a combination of Sephadex LH-20 permeation and silica gel chromatography and their chemical structures were elucidated by spectroscopic methods (NMR) and molecular modeling. The gastroprotective activity of the new compound 1 was evaluated on the HCl/EtOH-induced gastric lesion model in mice and compared to the activity showed by the known compounds. RESULTS: A new mulinane diterpene along with five known diterpenoids have been isolated from a Peruvian sample of A. compacta and the gastroprotective results show that compound 1 is less active than the other known mulinane diterpenoids isolated. CONCLUSIONS: A. compacta growing in Perú showed the presence of the new mulinane 1, which was poorly active in the HCl/EtOH-induced gastric lesion model in mice. Indeed, the activity was lower than other diterpenoids (2-6) showing an oxygenated function at C-16 or/and C-20, which confirm the role of an oxygenated group (OH or carboxylic acid) for the gastroprotective activity of mulinane compounds.